Environmental pollution of electronic waste recycling in India: A critical review - Awasthi, Abhishek Kumar; Zeng, Xianlai; Li, Jinhui (Environmental pollution (1987), 2016)
The rapid growth of the production of electrical and electronic products has meant an equally rapid growth in the amount of electronic waste (e-waste), much of which is illegally imported to India, for disposal presenting a serious environmental challenge. The environmental impact during e-waste recycling was investigated and metal as well as other pollutants [e.g. polybrominated diphenyl ethers (PBDEs), polychlorinated biphenyls (PCBs)] were found in excessive levels in soil, water and other habitats. The most e-waste is dealt with as general or crudely often by open burning, acid baths, with recovery of only a few materials of value. As resulted of these process; dioxins, furans, and heavy metals are released and harmful to the surrounding environment, engaged workers, and also residents inhabiting near the sites. The informal e-waste sectors are growing rapidly in the developing countries over than in the developed countries because of cheapest labor cost and week legislations systems. It has been confirmed that contaminates are moving through the food chain via root plant translocation system, to the human body thereby threatening human health. We have suggested some possible solution toward in which plants and microbes combine to remediate highly contaminated sites. •It systematically reviewed Environmental deterioration through e-waste recycling in India.•We found heavy metals (Cu, Pb, Cd and Cr) potentially serious concern at recycling site.•The heavy metals can entered human body through the direct and indirect exposure.•Regular monitoring required to examine the possibility of risk through e-waste mismanagement.•Further phytoremedial approach can be use as one of the possible solution for contaminated soil and improve the land quality. The e-waste recycling sites are highly contaminated with heavy metals as well as other pollutants (e.g. PBDEs, PCBs) in excessive levels.